The systemic roots of Russia's recession - Marek Dabrowski (Bruegel, 2015)
The Russian economy grew rapidly between 2000 and 2007, but growth decelerated after the 2008-09 global financial crisis, and since mid-2014 Russia has moved into recession. A number of short-term factors have caused recession: lower oil prices, the conflict with Ukraine, European Union and United States sanctions against Russia and Russian counter-sanctions. However Russia's negative output trends have deeper structural and institutional roots. They can be tracked back about a decade to when previous market-reform policies started to be reversed in favour of dirigisme, leading to further deterioration of the business and investment climate. Russia must address its short-term problems, but in the medium-to-long term it must deal with its fundamental structural and institutional disadvantages: oil and commodity dependence and an unfriendly business and investment climate underpinned by poor governance. Compared to many other commodity producers, Russia is better placed to diversify its economy, mostly due to its excellent human capital. Ruble depreciation makes this task easier.
Keywords: 330